A study on curcuminoid profile of Curcuma longa L. varieties as affected by processing method - Nuthan, R Priyanka, M Vasundhara, A Jayaram, D (Journal of Spices and Aromatic Crops, 2016)
An attempt was made to understand the variation in the curcuminoid profile of turmeric varieties. Eight cultivars namely, Local (check), IISR-Alleppey Supreme, IISR-Kedaram, IISR-Prabha, IISRPrathibha, Suvarna, Suguna and Sudharshana were utilized for the study. Curcuminoid content of fresh, dried and cured varieties after methanolic extraction and quantification through HPLC revealed that Local (check) turmeric in fresh form was significantly superior in curcuminoid content. IISR-Prabha and IISR-Prathibha in dry and cured form respectively, also exhibited high curcuminoid content.